Nonaqueous electrolyte storage element and method for producing same

By setting the initial irreversible capacity ratio of the positive to negative electrode to 1.15 or more, the cracking and isolation of silicon oxide particles are minimized, improving capacity retention and discharge voltage maintenance in non-aqueous electrolyte storage devices.

JP7600989B2Active Publication Date: 2024-12-17GS YUASA CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021537004
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-01
Filing Date
2020-07-22
Publication Date
2024-12-17
Estimated Expiration
2040-07-22

AI Technical Summary

Technical Problem

Silicon oxide particles in non-aqueous electrolyte storage devices crack or become isolated due to repeated expansion and contraction during charging and discharging, leading to a low capacity retention rate.

Method used

The ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is set to 1.15 or more, reducing the negative electrode potential and minimizing particle cracking and isolation, thereby improving capacity retention during charge/discharge cycles.

Benefits of technology

This approach enhances the capacity retention rate and discharge voltage maintenance in non-aqueous electrolyte storage devices using silicon oxide as the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600989000003
    Figure 0007600989000003
  • Figure 0007600989000004
    Figure 0007600989000004
  • Figure 0007600989000005
    Figure 0007600989000005
Patent Text Reader

Abstract

One aspect of the present invention is a non-aqueous electrolyte power storage device comprising a positive electrode and a negative electrode including silicon oxide, wherein the initial irreversible capacity of the positive electrode is 1.15 or more with respect to the initial irreversible capacity of the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element, a manufacturing method thereof, and an electricity storage device. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally include an electrode body having a pair of electrodes electrically isolated by a separator, and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring ions between the electrodes. In addition, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used as non-aqueous electrolyte storage elements other than secondary batteries.

[0003] As one of such nonaqueous electrolyte electricity storage elements, electricity storage elements using silicon oxide as the negative electrode active material have been developed (see Patent Documents 1 to 5). Silicon oxide has the advantage of having a larger capacity than carbon materials that are widely used as negative electrode active materials. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-113863 A [Patent Document 2] JP 2015-053152 A [Patent Document 3] JP 2014-120459 A [Patent Document 4] JP 2015-088462 A [Patent Document 5] International Publication No. 2012 / 169282 Summary of the Invention [Problem to be solved by the invention]

[0005] However, silicon oxide is prone to particle cracking and isolation due to repeated expansion and contraction accompanying charge and discharge, and therefore nonaqueous electrolyte storage elements using silicon oxide are known to have low capacity retention during charge and discharge cycles.

[0006] The present invention has been made in light of the above-mentioned circumstances, and an object of the present invention is to provide a nonaqueous electrolyte storage element that uses silicon oxide in the negative electrode and has an improved capacity retention rate during charge / discharge cycles, a method for producing such a nonaqueous electrolyte storage element, and an electricity storage device including such a nonaqueous electrolyte storage element. [Means for solving the problem]

[0007] One embodiment of the present invention made to solve the above problems is a nonaqueous electrolyte electricity storage element that includes a positive electrode and a negative electrode containing silicon oxide, in which the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.15 or more.

[0008] Another aspect of the present invention is a method for producing a nonaqueous electrolyte electricity storage element, the method comprising: preparing a positive electrode; preparing a negative electrode containing silicon oxide; and performing initial charging and discharging, wherein a ratio of an initial irreversible capacity of the positive electrode to an initial irreversible capacity of the negative electrode is 1.15 or more.

[0009] Another aspect of the present invention is an electricity storage device including a plurality of nonaqueous electrolyte storage elements, at least one of which is the nonaqueous electrolyte storage element according to one aspect of the present invention. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte electricity storage element that uses silicon oxide in a negative electrode and has an improved capacity retention rate in charge-discharge cycles, a method for manufacturing such a nonaqueous electrolyte electricity storage element, and an electricity storage device including such a nonaqueous electrolyte electricity storage element. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a diagram showing a schematic diagram of the initial charge / discharge curves of the positive electrode and the negative electrode of a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention and a conventional nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing the initial charge / discharge curve of the nonaqueous electrolyte storage element according to one embodiment of the present invention shown in FIG. 1, with the addition of an initial discharge curve of the negative electrode when the initial irreversible capacity ratio (Q'c / Q'a) is made larger. [Diagram 3] FIG. 3 is a transparent perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Figure 4] FIG. 4 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. [Diagram 5] FIG. 5 is a graph showing the relationship between the initial irreversible capacity ratio (Q'c / Q'a) and the capacity maintenance rate in charge-discharge cycles for each of the nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 6] FIG. 6 is a graph showing the relationship between the initial irreversible capacity ratio (Q'c / Q'a) of each of the nonaqueous electrolyte storage elements of Examples 3 to 6 and the average discharge voltage retention rate in the depth of discharge (DOD) range of 50% to 100% in the charge-discharge cycle. [Figure 7] FIG. 7 is a graph showing the relationship between the initial irreversible capacity ratio (Q'c / Q'a) of each of the nonaqueous electrolyte storage elements of Examples 3 to 6 and the energy retention rate in the depth of discharge (DOD) range of 50% to 100% in the charge-discharge cycle. [Figure 8] FIG. 8 is a graph showing the difference in discharge curves of a negative electrode depending on whether or not the accumulation of a highly crystalline phase, which will be described later, is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] One aspect of the present invention is a nonaqueous electrolyte electricity storage element (α) comprising a positive electrode and a negative electrode containing silicon oxide, in which the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.15 or more.

[0013] The nonaqueous electrolyte storage element (α) is a nonaqueous electrolyte storage element using silicon oxide for the negative electrode, and has an improved capacity retention rate in charge-discharge cycles. The reason for this effect is unclear, but the following is presumed. FIG. 1 is a diagram showing a schematic diagram of an initial charge-discharge curve of a conventional nonaqueous electrolyte storage element using silicon oxide for the negative electrode, and an initial charge-discharge curve of a nonaqueous electrolyte storage element (α) according to one embodiment of the present invention. In FIG. 1, the charge-discharge curve of the positive electrode and the charge curve of the negative electrode are the same for the conventional nonaqueous electrolyte storage element and the nonaqueous electrolyte storage element (α) according to one embodiment of the present invention. In FIG. 1, curve A represents the initial charge curve of the positive electrode, curve B represents the initial discharge curve of the positive electrode, curve C represents the initial charge curve of the negative electrode, curve (dashed line) d represents the initial discharge curve of the negative electrode of the conventional nonaqueous electrolyte storage element, and curve D represents the initial discharge curve of the negative electrode of the nonaqueous electrolyte storage element (α) according to one embodiment of the present invention. In addition, Qc represents the initial reversible capacity of the positive electrode, Q'c represents the initial irreversible capacity of the positive electrode, Qa represents the initial reversible capacity of the negative electrode of the nonaqueous electrolyte storage element (α) according to one embodiment of the present invention, Q'a represents the initial irreversible capacity of the negative electrode of the nonaqueous electrolyte storage element (α) according to one embodiment of the present invention, qa represents the initial reversible capacity of the negative electrode of the conventional nonaqueous electrolyte storage element, and q'a represents the initial irreversible capacity of the negative electrode of the conventional nonaqueous electrolyte storage element. In the conventional nonaqueous electrolyte storage element using silicon oxide as the negative electrode, as shown by the initial discharge curve d of the negative electrode, it is considered that the increase in the negative electrode potential (V1) at a depth of discharge (DOD) of 100% causes a decrease in the capacity retention rate in the charge-discharge cycle. That is, the amount of insertion and removal of lithium ions and the like accompanying charge and discharge in the negative electrode is large, and the change in the expansion and contraction of the negative electrode is large, which makes it easy for the particles to crack or become isolated, and reduces the capacity retention rate in the charge-discharge cycle of the nonaqueous electrolyte storage element. In contrast, in the nonaqueous electrolyte storage element (α) according to one embodiment of the present invention, the initial irreversible capacity (Q'c) of the positive electrode relative to the initial irreversible capacity (Q'a) of the negative electrode, i.e., the initial irreversible capacity ratio (Q'c / Q'a) is set to 1.15 or more, thereby lowering the negative electrode potential (V2) at 100% DOD.As a result, it is presumed that in the nonaqueous electrolyte storage element (α), the change in expansion and contraction of the silicon oxide particles is reduced, thereby suppressing cracking and isolation of the silicon oxide particles, thereby improving the capacity retention rate during charge-discharge cycles.

[0014] The initial irreversible capacity (initial irreversible capacity per unit area) of the positive electrode of the nonaqueous electrolyte storage element is the difference between the charge capacity and discharge capacity per unit area of ​​the positive electrode X (charge capacity-discharge capacity) when a single-electrode battery is charged and discharged, in which the part that faces the negative electrode and contributes to charging and discharging is the positive electrode X before charging and discharging, which is manufactured with the same formulation as the positive electrode of the nonaqueous electrolyte storage element, as the working electrode, and metal Li is used as the counter electrode. Similarly, the initial irreversible capacity (initial irreversible capacity per unit area) of the negative electrode of the nonaqueous electrolyte storage element is the difference between the charge capacity and discharge capacity per unit area of ​​the negative electrode X (charge capacity-discharge capacity) when a single-electrode battery is charged and discharged, in which the part that faces the positive electrode and contributes to charging and discharging is the negative electrode X before charging and discharging, which is manufactured with the same formulation as the negative electrode of the nonaqueous electrolyte storage element, as the working electrode, and metal Li is used as the counter electrode.

[0015] A specific method for measuring the charge capacity and discharge capacity of the positive electrode X is as follows. A single-electrode battery is assembled using the positive electrode X as a working electrode and metallic Li as a counter electrode, and one cycle of charge and discharge is performed as follows. A current equivalent to 0.1 C for the discharge capacity (mAh) of the positive electrode X calculated based on the theoretical discharge capacity (mAh / g) per mass of the positive electrode active material is set as a charging current, and the potential of the working electrode is set to the positive electrode potential (V vs. Li / Li) that the designer planned for the nonaqueous electrolyte storage element actually to be applied to reach when the SOC is 100%. + ), and then a constant potential charge is performed at that potential for a total charge time of 30 hours to determine the charge capacity. After a 10-minute rest period, a constant current discharge is performed with the same current value as the charging current as the discharge current, and the potential value of the working electrode is determined to be the positive electrode potential (V vs. Li / Li) that the designer planned the non-aqueous electrolyte storage element to actually be applied to reach when DOD is 100%. + When the value of ) is reached, discharge is terminated and the discharge capacity is calculated.

[0016] A specific method for measuring the charge capacity and discharge capacity of the negative electrode X is as follows. A single-electrode battery is assembled using the negative electrode X as a working electrode and metallic Li as a counter electrode, and one cycle of charge and discharge is performed. Here, the operation of passing a current in a direction in which the negative electrode X is electrochemically reduced is called charging, and the operation of passing a current in a direction in which the negative electrode X is electrochemically oxidized is called discharging. First, a current equivalent to 0.1 C is set as a charging current for the discharge capacity (mAh) of the negative electrode X calculated based on the theoretical discharge capacity (mAh / g) per mass of the negative electrode active material, and the potential of the working electrode is set to 0.02 V vs. Li / Li + After charging at a constant current until the potential reaches 2.0 V vs. Li / Li, a constant potential charge is performed at that potential for a total charge time of 30 hours, and the charge capacity is calculated. After a 10-minute rest period, a constant current discharge is performed with the same current value as the charging current as the discharge current, and when the potential of the working electrode reaches 2.0 V vs. Li / Li, + When this is reached, the discharge is terminated and the discharge capacity is calculated.

[0017] The open circuit potential of the negative electrode of the nonaqueous electrolyte storage element (α) at ​​100% DOD is 0.53 V vs. Li / Li + In this way, it is preferable that the open circuit potential of the negative electrode in the state of 100% DOD is 0.53 V vs. Li / Li + When the capacity retention rate is equal to or less than this value, the change in expansion and contraction of the silicon oxide particles becomes sufficiently small, and the capacity retention rate of the nonaqueous electrolyte electricity storage element (α) during charge and discharge cycles can be further increased.

[0018] The procedure for adjusting the nonaqueous electrolyte electricity storage element to a DOD of 100% is as follows. First, the nonaqueous electrolyte storage element is set to a state of SOC100%. To set the nonaqueous electrolyte storage element to a state of SOC100%, use the charging method specified for the nonaqueous electrolyte storage element. If there is a charger specifically for the nonaqueous electrolyte storage element, use it to fully charge it. If the charging method specified for the nonaqueous electrolyte storage element is unclear, first, a discharge current of 0.2C is used for the rated capacity (mAh) of the nonaqueous electrolyte storage element, constant current discharge is performed with an end voltage of 2.0V, and then the element is left for 10 minutes, and then a charge current of 0.02C is used to perform constant current charging for a charging time of 50 hours to fully charge the element. After charging is completed, the element is left for 10 minutes. Next, constant current discharge is performed with a current equivalent to 0.2 C as the discharge current. The discharge time is 5 hours. Through the above procedure, an amount of electricity equivalent to the rated capacity of the nonaqueous electrolyte storage element is discharged, and the nonaqueous electrolyte storage element is adjusted to a DOD of 100%. When the nonaqueous electrolyte storage element is not provided with a reference electrode, the sealing opening can be opened in an atmosphere with a dew point of -30°C or less in a state where the nonaqueous electrolyte storage element is adjusted to a DOD of 100%, and the negative electrode potential can be measured using the reference electrode.

[0019] It is preferable that the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.55 or less. By setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less in this way, the discharge voltage retention rate in the utilization region of silicon oxide in the charge / discharge cycle is improved. The reason for this effect is not clear, but the following is presumed. FIG. 2 is a diagram showing the initial charge / discharge curves A, B, C, and D of FIG. 1, with an additional curve (dashed line) D' in which the initial reversible capacity Qa is large and the initial irreversible capacity Q'a is small as the initial discharge curve of the negative electrode. As shown in FIG. 2, when the initial irreversible capacity ratio (Q'c / Q'a) is made larger, the negative electrode potential (V2 ’ In this case, even if the DOD reaches 100%, the lithium absorbed in the silicon oxide is not released completely, and the amorphous alloy phase (a-Li x S y ) will remain. a-Li x S yhas higher electronic conductivity than other phases in silicon oxide (a-Si), so a-Li x S y If you charge it while there is still a-Li x S y The reaction between and lithium progresses to c-Li 15 A highly crystalline phase, which is presumably due to the formation of Si4, is easily generated. The highly crystalline phase accumulates with repeated charging and discharging, and the discharge voltage gradually decreases. In this way, if the negative electrode potential in the state of 100% DOD is too low, the accumulation of the highly crystalline phase accompanying repeated charging and discharging reduces the discharge voltage retention rate in the region in which silicon oxide is used. In contrast, if the negative electrode potential in the state of 100% DOD is relatively high, even if the highly crystalline phase is formed, it returns to a-Si during discharge, so that the accumulation of the highly crystalline phase is unlikely to occur. In this way, by setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less, the a-Li x S y It is presumed that the residual amount of the silicon oxide is reduced and the accumulation of the highly crystalline phase is suppressed, resulting in an improvement in the discharge voltage retention rate in the region where silicon oxide is used. In addition, by setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less in this way and suppressing the progression of the accumulation of the highly crystalline phase, it is possible to suppress the change in the shape of the discharge curve and the decrease in the discharged energy that accompanies repeated charging and discharging. Furthermore, by setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less, the capacity retention rate during charge and discharge cycles tends to be further increased.

[0020] The open circuit potential of the negative electrode of the nonaqueous electrolyte storage element (α) at ​​100% DOD is 0.485 V vs. Li / Li + In this way, the open circuit potential of the negative electrode in the state of 100% DOD is preferably 0.485 V vs. Li / Li + As a result of the above, accumulation of the highly crystalline phase is further suppressed, and the discharge voltage retention rate in the utilization region of silicon oxide during charge and discharge cycles is further improved.

[0021] Another embodiment of the present invention is a nonaqueous electrolyte electricity storage element (β) comprising a positive electrode and a negative electrode containing silicon oxide, in which the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.55 or less.

[0022] Conventional nonaqueous electrolyte storage elements using silicon oxide for the negative electrode may experience a drop in discharge voltage due to accumulation of the highly crystalline phase during charge and discharge cycles. Another aspect of the present invention has been made based on such circumstances, and aims to provide a nonaqueous electrolyte storage element using silicon oxide for the negative electrode, which has an improved discharge voltage retention rate in the region where silicon oxide is used during charge and discharge cycles. That is, the nonaqueous electrolyte storage element (β) is a nonaqueous electrolyte storage element using silicon oxide for the negative electrode, which has an improved discharge voltage retention rate in the region where silicon oxide is used during charge and discharge cycles. The reason why such an effect occurs is unclear, but as described above, it is presumed that by setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less, accumulation of the highly crystalline phase is suppressed, and as a result, the discharge voltage retention rate in the region where silicon oxide is used is improved.

[0023] The open circuit potential of the negative electrode of the nonaqueous electrolyte storage element (β) at 100% DOD is 0.485 V vs. Li / Li + In such a case, the discharge voltage retention rate in the utilization region of silicon oxide during charge and discharge cycles is further improved.

[0024] In the nonaqueous electrolyte storage element (α) and the nonaqueous electrolyte storage element (β), the negative electrode may further contain graphite. Since the operating potential region of graphite is lower than that of silicon oxide, the discharge reaction between graphite and silicon oxide is not substantially a competitive reaction. Therefore, in both cases where the negative electrode contains only silicon oxide and where the negative electrode contains silicon oxide and graphite, the effect of increasing the capacity retention rate in the charge-discharge cycle of the nonaqueous electrolyte storage element by setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.15 or more is obtained, and the effect of increasing the discharge voltage retention rate in the utilization region of silicon oxide in the charge-discharge cycle of the nonaqueous electrolyte storage element by setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less is obtained.

[0025] In addition, "graphite" refers to a material that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. The "discharged state" of graphite refers to a state in which the open circuit voltage is 0.7 V or more in a single-electrode battery using a negative electrode containing graphite as a negative electrode active material as a working electrode and metallic Li as a counter electrode. Since the potential of the metallic Li counter electrode in the open circuit state is approximately equal to the oxidation-reduction potential of Li, the open circuit voltage in the single-electrode battery is approximately equal to the potential of the negative electrode containing graphite relative to the oxidation-reduction potential of Li. In other words, an open circuit voltage of 0.7 V or more in the single-electrode battery means that sufficient lithium ions that can be absorbed and released during charging and discharging are released from the graphite, which is the negative electrode active material.

[0026] In the nonaqueous electrolyte storage element (α) and the nonaqueous electrolyte storage element (β), the positive electrode preferably contains a lithium transition metal composite oxide having an α-NaFeO2 crystal structure or a spinel crystal structure. When the positive electrode contains such a positive electrode active material, the discharge capacity of the nonaqueous electrolyte storage element (α) and the nonaqueous electrolyte storage element (β) can be increased.

[0027] Another aspect of the present invention is a method (α) for producing a nonaqueous electrolyte storage element, comprising preparing a positive electrode, preparing a negative electrode containing silicon oxide, and performing initial charging and discharging, wherein the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.15 or more.

[0028] According to the production method (α), it is possible to produce a nonaqueous electrolyte electricity storage element that uses silicon oxide in the negative electrode and has an improved capacity retention rate during charge-discharge cycles.

[0029] Another aspect of the present invention is a method (β) for producing a nonaqueous electrolyte storage element, comprising preparing a positive electrode, preparing a negative electrode containing silicon oxide, and performing initial charging and discharging, wherein the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.55 or less.

[0030] According to the production method (β), it is possible to produce a nonaqueous electrolyte storage element that uses silicon oxide in the negative electrode, and that has an improved discharge voltage retention rate in the utilization range of silicon oxide in charge and discharge cycles.

[0031] Another aspect of the present invention is an electricity storage device comprising a plurality of nonaqueous electrolyte electricity storage elements, at least one of which is the nonaqueous electrolyte electricity storage element (α) or the nonaqueous electrolyte electricity storage element (β). The electricity storage device has a high capacity retention rate in charge / discharge cycles or a high discharge voltage retention rate in the utilization region of silicon oxide.

[0032] A nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, a method for producing the same, and an electricity storage device will be described in detail below.

[0033] <Non-aqueous electrolyte electricity storage element> The nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode, and a nonaqueous electrolyte. Hereinafter, a secondary battery will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are usually stacked or wound alternately with a separator interposed therebetween to form an electrode body. This electrode body is housed in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the container, a known metal container, a resin container, or the like that is usually used as a container for a secondary battery can be used.

[0034] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0035] The positive electrode substrate has electrical conductivity. The term "electrically conductive" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7 It means that the resistance is more than Ω·cm. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc. or alloys thereof are used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. As the positive electrode substrate, foil, vapor deposition film, etc. can be mentioned, and foil is preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085, A3003, etc. specified in JIS-H-4000 (2014).

[0036] The lower limit of the average thickness of the positive electrode substrate is preferably 5 μm, more preferably 10 μm. The upper limit of the average thickness of the positive electrode substrate is preferably 50 μm, more preferably 40 μm. By making the average thickness of the positive electrode substrate equal to or greater than the lower limit, the strength of the positive electrode substrate can be increased. By making the average thickness of the positive electrode substrate equal to or less than the upper limit, the energy density per volume of the secondary battery can be increased. For these reasons, it is preferable that the average thickness of the positive electrode substrate is equal to or greater than any of the lower limits and equal to or less than any of the upper limits. The term "average thickness" refers to the average value of thicknesses measured at any ten points. The term "average thickness" is defined in the same manner when used for other members, etc.

[0037] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and includes, for example, a resin binder and conductive particles. The intermediate layer includes, for example, conductive particles such as carbon particles, thereby reducing the contact resistance between the positive electrode substrate and the positive electrode active material layer.

[0038] The positive electrode active material layer contains a positive electrode active material. The positive electrode active material layer is usually a layer formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.

[0039] The positive electrode active material can be appropriately selected from known positive electrode active materials that are usually used for lithium ion secondary batteries and the like. As the positive electrode active material, a material capable of absorbing and releasing lithium ions is usually used. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Niγ Mn β Co (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4,Li x Ni γ Mn (2-γ) Examples of the polyanion compound include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of the chalcogen compound include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. In the positive electrode active material layer, one of these positive electrode active materials may be used alone, or two or more may be mixed and used.

[0040] The positive electrode active material is preferably a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure or a spinel type crystal structure, more preferably a lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, and Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1) is more preferred. In the above formula, the lower limit of x may be preferably 0, more preferably greater than 0, and more preferably 0.1. The upper limit of x may be preferably 0.4, and more preferably 0.3. The lower limit of the value of γ may be preferably 0.3, and more preferably 0.5. The upper limit of the value of γ may be preferably 0.9, and more preferably 0.8. The lower limit of the value of β may be preferably 0.1, and more preferably 0.3, and more preferably 0.4, and even more preferably 0.5. The upper limit of the value of 1-x-γ-β may be preferably 1.0, and more preferably 0.4, and even more preferably 0.1. 1-x-γ-β=0 may also be possible.

[0041] The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. Here, the "average particle size" refers to a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0042] In order to obtain particles of the positive electrode active material or the like in a predetermined shape, a pulverizer, a classifier, or the like is used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. When pulverizing, wet pulverization in which water or an organic solvent such as hexane is present can also be used. As a classification method, a sieve, a wind classifier, or the like is used as necessary for both dry and wet methods.

[0043] The lower limit of the content of the positive electrode active material in the positive electrode active material layer is preferably 70 mass%, more preferably 80 mass%, and even more preferably 90 mass%. The upper limit of the content of the positive electrode active material is preferably 98 mass%, and more preferably 96 mass%. By setting the content of the positive electrode active material within the above range, the electric capacity of the secondary battery can be increased. The content of the positive electrode active material in the positive electrode active material layer can be set to be equal to or higher than any of the above lower limits and equal to or lower than any of the above upper limits.

[0044] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include graphite; carbon black such as furnace black and acetylene black; metals; and conductive ceramics. The conductive agent may be in the form of powder or fiber. Among these, acetylene black is preferred from the viewpoint of electronic conductivity and coatability.

[0045] The lower limit of the conductive agent content in the positive electrode active material layer is preferably 1 mass %, more preferably 2 mass %. The upper limit of the conductive agent content is preferably 10 mass %, more preferably 5 mass %. By setting the conductive agent content within the above range, the electric capacity of the secondary battery can be increased. For these reasons, the conductive agent content is preferably equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.

[0046] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0047] The lower limit of the binder content in the positive electrode active material layer is preferably 0.5% by mass, more preferably 2% by mass. The upper limit of the binder content is preferably 10% by mass, more preferably 5% by mass. By setting the binder content within the above range, the active material can be stably maintained. For these reasons, the binder content is preferably equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0048] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.

[0049] The filler is not particularly limited, and examples of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, glass, and alumina silicate.

[0050] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0051] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer of the negative electrode is not particularly limited and may be the same as that of the intermediate layer of the positive electrode.

[0052] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils and vapor-deposited films, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0053] The lower limit of the average thickness of the negative electrode substrate is preferably 3 μm, more preferably 5 μm. The upper limit of the average thickness of the negative electrode substrate is preferably 30 μm, more preferably 20 μm. By making the average thickness of the negative electrode substrate equal to or greater than the above lower limits, the strength of the negative electrode substrate can be increased. By making the average thickness of the negative electrode substrate equal to or less than the above upper limits, the energy density per volume of the secondary battery can be increased. For these reasons, it is preferable that the average thickness of the negative electrode substrate is equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0054] The negative electrode active material layer contains silicon oxide which is the negative electrode active material. The negative electrode active material layer is usually a layer formed from a so-called negative electrode mixture containing the negative electrode active material. The negative electrode mixture forming the negative electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as required. As the optional components such as the conductive agent, the binder, the thickener, and the filler, those similar to those in the positive electrode active material layer can be used. The content of each of these optional components in the negative electrode active material layer can be within the range described as the content of these in the positive electrode active material and the like.

[0055] Silicon oxide usually exists as particles. Silicon oxide is usually a compound represented by SiO x (0 < x < 2). The lower limit of the above x is preferably 0.8. Also, the upper limit of the above x is preferably 1.2. The particles of silicon oxide may be those in which silicon (Si) and silicon dioxide (SiO2) coexist. The average particle size of silicon oxide is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of silicon oxide to be not less than the above lower limit, the initial irreversible capacity (μAh / g) per unit mass of silicon oxide tends to be small, so it becomes easier to design such that the irreversible capacity of the positive electrode with respect to the initial irreversible capacity of the negative electrode becomes a large value. By setting the average particle size of silicon oxide to be not more than the above upper limit, the electron conductivity of the negative electrode active material layer is improved. It is preferable to use silicon oxide as the negative electrode active material by appropriately carbon coating the particle surface by a CVD method or the like for the purpose of imparting electron conductivity.

[0056] The lower limit of the silicon oxide content in the negative electrode active material is preferably 1 mass%, more preferably 2 mass%, and even more preferably 4 mass% in some cases. By making the silicon oxide content equal to or greater than the above lower limits, it is possible to increase the discharge capacity of the secondary battery. On the other hand, the upper limit of this content may be, for example, 100 mass%, but is preferably 30 mass%, more preferably 15 mass%, and even more preferably 8 mass% in some cases. By making the silicon oxide content equal to or less than the above upper limits, it is possible to further increase the capacity retention rate in the charge / discharge cycle of the secondary battery. The silicon oxide content in the negative electrode active material can be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0057] The negative electrode active material layer preferably further contains graphite as a negative electrode active material. By containing graphite as a negative electrode active material, the capacity retention rate in the charge / discharge cycle of the secondary battery is further increased. Examples of graphite include natural graphite and artificial graphite. From the viewpoint of obtaining a material with stable physical properties, artificial graphite is preferable. The average particle size of graphite can be, for example, 1 μm or more and 100 μm or less.

[0058] The lower limit of the graphite content in the negative electrode active material may be, for example, 1% by mass, but may be preferably 70% by mass, more preferably 85% by mass, and even more preferably 92% by mass. By making the graphite content equal to or greater than the above lower limit, it is possible to further increase the capacity retention rate in the charge / discharge cycle of the secondary battery. On the other hand, the upper limit of this content is preferably 99% by mass, more preferably 98% by mass, and even more preferably 96% by mass. By making the graphite content equal to or less than the above upper limit, it is possible to increase the discharge capacity of the secondary battery. The graphite content in the negative electrode active material may be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0059] When the negative electrode active material contains silicon oxide and graphite, the lower limit of the content of silicon oxide in the total content of silicon oxide and graphite is preferably 1 mass%, more preferably 2 mass%, and even more preferably 4 mass% in some cases. By making the content of silicon oxide equal to or more than the above lower limit, the discharge capacity of the secondary battery can be increased. On the other hand, the upper limit of this content may be, for example, 99 mass%, but is preferably 30 mass%, more preferably 15 mass%, and even more preferably 8 mass% in some cases. By making the content of silicon oxide equal to or less than the above upper limit, the capacity retention rate in the charge / discharge cycle of the secondary battery can be further increased. The content of silicon oxide in the total content of silicon oxide and graphite can be equal to or more than any of the above lower limits and equal to or less than any of the above upper limits.

[0060] The negative electrode active material may further contain a known negative electrode active material that is generally used in lithium ion secondary batteries, etc., other than silicon oxide and graphite. However, the lower limit of the total content of silicon oxide and graphite in the negative electrode active material is preferably 90 mass%, more preferably 99 mass%. On the other hand, the upper limit of this total content may be 100 mass%. In this way, the effect of the present invention is more fully achieved by using only silicon oxide or only silicon oxide and graphite as the negative electrode active material.

[0061] The lower limit of the total content of the negative electrode active material in the negative electrode active material layer is preferably 70 mass%, more preferably 80 mass%, and even more preferably 90 mass%. The upper limit of the total content of the negative electrode active material is preferably 98 mass%, and more preferably 97 mass%. By setting the total content of the negative electrode active material within the above range, the electric capacity of the secondary battery can be increased.

[0062] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, and Ge, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0063] (Separator) As the separator, for example, a woven fabric, a nonwoven fabric, a porous resin film, etc. are used. Among these, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of non-aqueous electrolyte retention. As the main component of the separator, a polyolefin such as polyethylene or polypropylene is preferable from the viewpoint of strength, and a polyimide or aramid is preferable from the viewpoint of oxidation decomposition resistance. These resins may also be combined.

[0064] An inorganic layer may be disposed between the separator and the electrode (usually, the positive electrode). This inorganic layer is a porous layer also called a heat-resistant layer. A separator having an inorganic layer formed on one or both surfaces of a porous resin film may also be used. The inorganic layer is usually composed of inorganic particles and a binder, and may contain other components. As the inorganic particles, Al2O3, SiO2, aluminosilicate, etc. are preferable.

[0065] (Non-aqueous electrolyte) The nonaqueous electrolyte may be a known nonaqueous electrolyte that is commonly used in a general nonaqueous electrolyte secondary battery (nonaqueous electrolyte storage element). The nonaqueous electrolyte may include, for example, a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.

[0066] The non-aqueous solvent may be a known non-aqueous solvent that is generally used as a non-aqueous solvent for a general non-aqueous electrolyte for a storage element. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, esters, ethers, amides, sulfones, lactones, and nitriles. Among these, it is preferable to use at least a cyclic carbonate or a chain carbonate, and it is more preferable to use a cyclic carbonate and a chain carbonate in combination. When a cyclic carbonate and a chain carbonate are used in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is not particularly limited, but is preferably 5:95 or more and 50:50 or less.

[0067] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate, with EC being preferred.

[0068] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, and the like. Among these, EMC is preferable.

[0069] The electrolyte salt may be any known electrolyte salt that is commonly used as an electrolyte salt for a general non-aqueous electrolyte for a storage element, such as lithium salt, sodium salt, potassium salt, magnesium salt, onium salt, etc., with lithium salt being preferred.

[0070] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having a fluorohydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0071] The lower limit of the content of the electrolyte salt in the nonaqueous electrolyte is 0.1 mol / dm 3 is preferred, and 0.3 mol / dm 3 More preferably, 0.5 mol / dm 3 More preferably, 0.7 mol / dm 3On the other hand, the upper limit is not particularly limited, but is preferably 2.5 mol / dm 3 is preferred, and 2 mol / dm 3 More preferably, 1.5 mol / dm 3 The content of the electrolyte salt is preferably equal to or more than any one of the above lower limits and equal to or less than any one of the above upper limits.

[0072] The non-aqueous electrolyte may contain other additives. As the non-aqueous electrolyte, a room temperature molten salt, an ionic liquid, a polymer solid electrolyte, or the like may also be used.

[0073] (Initial irreversible capacity ratio (Q'c / Q'a)) In the first embodiment of the present invention, the lower limit of the initial irreversible capacity ratio (Q'c / Q'a: the initial irreversible capacity per unit area of ​​the positive electrode (Q'c) relative to the initial irreversible capacity per unit area of ​​the negative electrode (Q'a)) of the secondary battery (nonaqueous electrolyte storage element) is 1.15, and may be preferably 1.20. By making the initial irreversible capacity of the negative electrode relatively small in this way, it is possible to suppress the increase in the negative electrode potential at or near DOD 100% as described above, and to increase the capacity maintenance rate in the charge-discharge cycle of the nonaqueous electrolyte storage element. The upper limit of the initial irreversible capacity ratio (Q'c / Q'a) is, for example, 2.5, may be 2.0, or may be 1.6, is preferably 1.55, is more preferably 1.50, is even more preferably 1.45, and is even more preferably 1.40. By making the initial irreversible capacity ratio (Q'c / Q'a) equal to or less than the above upper limit, it is possible to improve the discharge voltage maintenance rate in the utilization region of silicon oxide in the charge-discharge cycle as described above. In addition, the initial irreversible capacity ratio (Q'c / Q'a) can be set to be equal to or higher than any one of the above lower limits and equal to or lower than any one of the above upper limits.

[0074] Methods for making the initial irreversible capacity ratio (Q'c / Q'a) 1.15 or more include (1) reducing the mass of the negative electrode active material per unit area (i.e., the capacity of the negative electrode) relatively to the mass of the positive electrode active material (i.e., the capacity of the positive electrode), and (2) doping the negative electrode active material with lithium or the like in advance.

[0075] Specific examples of the above (1) method include relatively reducing the amount of negative electrode mixture containing the negative electrode active material applied per unit area, reducing the ratio of the negative electrode active material in the negative electrode mixture, reducing the ratio of silicon oxide when silicon oxide and graphite are used in combination as the negative electrode active material, etc. In addition, since this is a relative relationship with the mass of the positive electrode active material (positive electrode capacity), the type of positive electrode active material and the mass per unit area may be adjusted.

[0076] Regarding the above (1), the upper limit of the ratio (N / P) of the initial charge capacity (N) per unit area of ​​the negative electrode to the initial charge capacity (P) per unit area of ​​the positive electrode is preferably 1.20, more preferably 1.15. By setting the initial charge capacity ratio (N / P) to the above upper limit or less, and preferably by using a combination of a predetermined positive electrode active material and a negative electrode active material, the initial irreversible capacity ratio (Q'c / Q'a) can be easily adjusted to 1.15 or more. The lower limit of this initial charge capacity ratio (N / P) may be, for example, 0.7, but is preferably 1.00, more preferably 1.05. In addition, the initial charge capacity ratio (N / P) can be set to be equal to or greater than any of the above lower limits and equal to or less than any of the above upper limits.

[0077] Specific examples of the above method (2) include a chemical method using a reducing agent and an electrochemical method. Examples of reducing agents used in the chemical method include metallic lithium, as well as alkyl lithium such as propyl lithium and butyl lithium. In the electrochemical method, an electrode containing silicon oxide is prepared, and a current is passed in the charging direction to the electrode containing silicon oxide with lithium as a counter electrode, thereby obtaining silicon oxide doped with an arbitrary amount of lithium. The electrode containing silicon oxide doped with lithium in this way can be taken out and combined with a positive electrode to form a secondary battery.

[0078] Conversely, if one wishes to reduce the initial irreversible capacity ratio (Q'c / Q'a), for example, the mass of the negative electrode active material per unit area in (1) above can be increased relative to the mass of the positive electrode active material, and the amount of lithium or the like doped into the negative electrode active material in (2) above can be reduced.

[0079] In the second embodiment of the present invention, the upper limit of the initial irreversible capacity ratio (Q'c / Q'a) of the secondary battery (non-aqueous electrolyte storage element) is 1.55, preferably 1.50, more preferably 1.45, and even more preferably 1.40. By setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less, the accumulation of the highly crystalline phase is suppressed as described above, and the discharge voltage retention rate in the utilization region of silicon oxide in the charge / discharge cycle can be improved. In addition, by setting the initial irreversible capacity ratio (Q'c / Q'a) to 1.55 or less, the change in the shape of the discharge curve and the decrease in the discharged energy due to repeated charge / discharge are suppressed, and the capacity retention rate also tends to increase. The lower limit of the initial irreversible capacity ratio (Q'c / Q'a) in the secondary battery according to the second embodiment is not particularly limited, but it is preferably equal to or greater than the lower limit described as the first embodiment.

[0080] (Negative electrode potential at 100% DOD) The upper limit of the negative electrode potential in the secondary battery (non-aqueous electrolyte storage element) in a state of DOD 100% is, for example, 0.58 V vs. Li / Li + However, 0.53V vs. Li / Li+ is preferable, 0.51V vs.Li / Li + is more preferable, 0.50V vs. Li / Li + In this way, by setting the negative electrode potential at 100% DOD to the upper limit or less, the capacity retention rate of the nonaqueous electrolyte storage element during the charge-discharge cycle can be further increased. On the other hand, the lower limit of the negative electrode potential is, for example, 0.3 V vs. Li / Li + is preferable, and 0.4V vs. Li / Li + is more preferable, 0.45V vs. Li / Li + is more preferable, and 0.485V vs. Li / Li + is even more preferable. By setting the negative electrode potential at 100% DOD to be equal to or higher than the above lower limit, it is possible to improve the discharge voltage retention rate in the utilization region of silicon oxide in the charge / discharge cycle, and to increase the capacity of the secondary battery. In addition, the negative electrode potential at 100% DOD can be set to be equal to or higher than any of the above lower limits and equal to or lower than any of the above upper limits.

[0081] The configuration of the nonaqueous electrolyte storage element according to the present invention is not particularly limited, and examples include a cylindrical battery, a prismatic battery (rectangular battery), a flat battery, a coin battery, and a button battery.

[0082] FIG. 3 shows an outline of a rectangular nonaqueous electrolyte storage element 1 (nonaqueous electrolyte secondary battery) which is one embodiment of the nonaqueous electrolyte storage element according to the present invention. The figure is a see-through view of the inside of a container. In the nonaqueous electrolyte storage element 1 shown in FIG. 3, an electrode body 2 is housed in a container 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode active material and a negative electrode having a negative electrode active material with a separator interposed therebetween. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 4', and the negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 5'.

[0083] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The nonaqueous electrolyte storage element according to the first embodiment of the present invention can be produced by a method including preparing a positive electrode, preparing a negative electrode containing silicon oxide, and performing initial charging and discharging, wherein the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.15 or more.

[0084] The method for setting the initial irreversible capacity ratio of the positive electrode and the negative electrode (Q'c / Q'a: the initial irreversible capacity of the positive electrode (Q'c) relative to the initial irreversible capacity of the negative electrode (Q'a)) to 1.15 or more is as described above. Specific design procedures for the initial irreversible capacity ratio (Q'c / Q'a) include, for example, the following procedure. (1) Depending on the type and composition of the positive electrode active material, the potential of the positive electrode in a state of 100% SOC and the potential of the positive electrode in a state of 100% DOD are set. (2) With the initial reversible capacity (mAh / g) and the initial irreversible capacity (mAh / g) per unit mass of the positive electrode active material used being known, the prescription of the electrode density, porosity, thickness, etc. of the positive electrode active material layer provided in the positive electrode actually used in the nonaqueous electrolyte storage element is designed so that the initial irreversible capacity ratio (Q'c / Q'a) is as designed in relation to the negative electrode, and the positive electrode is fabricated. For confirmation, the positive electrode prepared is used, and the potential of the positive electrode set in (1) above is set as the upper limit potential for charging and the end potential for discharging, and the charge capacity and discharge capacity are measured according to the above-mentioned method for measuring the charge capacity and discharge capacity. The initial irreversible capacity per unit area of ​​the positive electrode is calculated from the difference between the measured charge capacity and discharge capacity. (3) Similarly, the initial reversible capacity (mAh / g) and the initial irreversible capacity (mAh / g) per unit mass of the negative electrode active material used are known, and the electrode density, porosity, thickness, etc. of the negative electrode active material layer provided in the negative electrode actually used in the nonaqueous electrolyte storage element are designed so that the initial irreversible capacity ratio (Q'c / Q'a) in relation to the positive electrode is as designed, and the negative electrode is prepared. For confirmation, the lower limit potential for charging is set to 0.02 V (vs. Li / Li + ), and the discharge end potential was 2.0 V (vs. Li / Li +) and measure the charge capacity and discharge capacity according to the above-mentioned method for measuring charge capacity and discharge capacity. The initial irreversible capacity per unit area of ​​the negative electrode is calculated from the difference between the measured charge capacity and discharge capacity. (4) Based on the calculated initial irreversible capacity per unit area of ​​the positive electrode and the initial irreversible capacity per unit area of ​​the negative electrode, it is confirmed that a nonaqueous electrolyte storage element can be fabricated in which the initial irreversible capacity ratio (Q'c / Q'a) is as designed.

[0085] The positive electrode and the negative electrode of the nonaqueous electrolyte storage element can be manufactured by a conventional method, except that the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.15 or more. The positive electrode can be manufactured, for example, by applying a positive electrode mixture paste to a positive electrode substrate directly or through an intermediate layer, and drying the paste. The positive electrode mixture paste includes each component constituting a positive electrode active material layer (positive electrode mixture), such as a positive electrode active material, and a dispersion medium. Similarly, the negative electrode can be manufactured, for example, by applying a negative electrode mixture paste to a negative electrode substrate directly or through an intermediate layer, and drying the paste. The negative electrode mixture paste includes each component constituting a negative electrode active material layer (negative electrode mixture), such as a negative electrode active material containing silicon oxide, and a dispersion medium.

[0086] The manufacturing method may include, as a step after the production of the positive electrode and the negative electrode, forming an electrode body in which the positive electrode and the negative electrode are alternately stacked by stacking or rolling them with a separator interposed therebetween, housing the positive electrode and the negative electrode (electrode body) in a container, injecting a nonaqueous electrolyte into the container through an inlet, and sealing the inlet. After assembling the nonaqueous electrolyte storage element before initial charging and discharging in this manner, initial charging and discharging can be performed. By going through the initial charging and discharging, for example, a nonaqueous electrolyte storage element in which the negative electrode potential in the state of DOD 100% in FIG. 1 is V2 can be obtained. Note that the "initial charging and discharging" refers to the first charging and discharging of a nonaqueous electrolyte storage element (non-charged and discharged nonaqueous electrolyte storage element) that has never been charged or discharged after assembly. The number of charge and discharge cycles in the initial charging and discharging may be one or two, or may be three or more.

[0087] A nonaqueous electrolyte storage element according to a second embodiment of the present invention can be manufactured by a method including preparing a positive electrode, preparing a negative electrode containing silicon oxide, and performing initial charging and discharging, and the ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.55 or less. A specific and preferred embodiment of the manufacturing method is the same as the method of manufacturing the nonaqueous electrolyte storage element according to the first embodiment described above, except that the initial irreversible capacity ratio (Q'c / Q'a) of the positive electrode and the negative electrode is 1.55 or less and the lower limit is not limited. A specific design procedure for setting the initial irreversible capacity ratio (Q'c / Q'a) of the positive electrode and the negative electrode to a predetermined value of 1.55 or less is also the same as the above-mentioned design procedure.

[0088] <Electricity storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage device comprising a plurality of nonaqueous electrolyte storage elements 1 in a power source for an automobile such as an electric vehicle (EV), a hybrid electric vehicle (HEV), or a plug-in hybrid electric vehicle (PHEV), a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technique of the present invention may be applied to at least one nonaqueous electrolyte storage element included in the electricity storage device.

[0089] 4 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte storage elements 1, are further assembled. That is, the electricity storage device 30 has a plurality of electricity storage units 20. Each electricity storage unit 20 has a plurality of nonaqueous electrolyte storage elements 1. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte storage elements.

[0090] <Other embodiments> The present invention is not limited to the above embodiment, and can be embodied in various modified and improved forms in addition to the above embodiment. For example, the positive electrode or the negative electrode does not need to have an intermediate layer. In addition, the positive electrode and the negative electrode of the nonaqueous electrolyte storage element do not need to have a clear layer structure. For example, the positive electrode may have a structure in which a positive electrode active material is supported on a mesh-shaped positive electrode base material.

[0091] In the above embodiment, the nonaqueous electrolyte storage element is mainly a nonaqueous electrolyte secondary battery, but the nonaqueous electrolyte storage element may be another type of nonaqueous electrolyte storage element, such as a capacitor (electric double layer capacitor, lithium ion capacitor, etc.). EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0093] [Example 1] (Measurement of irreversible capacity per unit mass of positive electrode active material) The positive electrode active material is LiNi, a lithium transition metal composite oxide with an α-NaFeO2 type crystal structure. 1 / 2 Mn 3 / 10 Co 1 / 5 O2 was prepared. This positive electrode active material has an upper limit charge potential of 4.33 V vs. Li / Li + The discharge end potential is 2.85 V vs. Li / Li + In this case, the initial charge capacity is 191.0 mAh / g, the initial discharge capacity is 166.9 mAh / g, and the initial irreversible capacity is 24.1 mAh / g.

[0094] (Measurement of irreversible capacity per unit mass of negative electrode active material) A mixture of silicon oxide (SiO) and graphite (Gr) was prepared as the negative electrode active material. The content of silicon oxide relative to the total amount of silicon oxide and graphite was 2.5 mass%. This negative electrode active material had a minimum charge potential of 0.02 V vs. Li / Li +The discharge end potential is 2.0 V vs. Li / Li + In this case, the initial charge capacity is 410.0 mAh / g, the initial discharge capacity is 374.3 mAh / g, and the initial irreversible capacity is 35.7 mAh / g.

[0095] (Preparation of positive and negative electrodes) A positive electrode mixture paste was prepared containing the positive electrode active material, acetylene black (AB), and polyvinylidene fluoride (PVDF) in a ratio of 93:3.5:3.5 (solid weight equivalent) and N-methylpyrrolidone (NMP) as a dispersion medium. This positive electrode mixture paste was applied to a strip of aluminum foil as a positive electrode substrate and dried to remove the NMP. 2 The amount of positive electrode mixture paste applied per electrode is 19.1 mg / cm2 in terms of solid content. 2 This was pressed with a roller press to form a positive electrode active material layer, which was then dried under reduced pressure to obtain a positive electrode. 2 The initial charge capacity (P) per 2 , 1cm 2 The initial irreversible capacity (Q'c) per 2 It became.

[0096] A negative electrode mixture paste was prepared containing the negative electrode active material (SiO+Gr):styrene butadiene rubber (SBR):carboxymethyl cellulose (CMC) in a mass ratio of 97:2:1 (solid content equivalent) and using water as a dispersion medium. This negative electrode mixture paste was applied to both sides of a strip-shaped copper foil current collector as a negative electrode substrate, and then dried to remove the water. 2 The amount of negative electrode mixture paste applied per unit area is 9.8 mg / cm2 in terms of solid content. 2 This was pressed with a roller press to form a negative electrode active material layer, which was then dried under reduced pressure to obtain a negative electrode. 2 The initial charge capacity per unit (N) is 3897.5 μAh / cm 2 , 1cm 2 The initial irreversible capacity (Q'a) per 2 It became.

[0097] The ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode thus obtained (Q'c / Q'a) was 1.26. 2 First charge capacity (P) per cm of negative electrode 2 The ratio (N / P) of the initial charge capacity (N) per cell was 1.15.

[0098] (Preparation of non-aqueous electrolyte) A non-aqueous solvent consisting of a mixture of EC, EMC, and DMC in a volume ratio of 30:35:35 was added with 1.0 mol / dm lithium hexafluorophosphate (LiPF6) as an electrolyte salt. 3 A non-aqueous electrolyte was prepared by mixing the above components so as to obtain a content of 100% by weight.

[0099] (Fabrication of non-aqueous electrolyte storage element) A polyolefin microporous film having an inorganic layer formed on one side was prepared as a separator. The positive electrode and the negative electrode were laminated with the separator interposed therebetween to prepare an electrode assembly. The electrode assembly was placed in a container made of a metal resin composite film, and the nonaqueous electrolyte was poured into the container, which was then sealed by heat welding.

[0100] (Initial charge / discharge) The obtained non-aqueous electrolyte storage element before charging and discharging was subjected to three cycles of initial charging and discharging at 25 ° C. in the following manner. In the first cycle, constant current constant voltage charging was performed with a charging current of 0.2 C, a charging end voltage of 4.25 V, and a total charging time of 7 hours, and then a rest period of 10 minutes was provided. Then, constant current discharging was performed with a discharging current of 0.2 C and a discharging end voltage of 2.75 V, and then a rest period of 10 minutes was provided. In the second and third cycles, constant current constant voltage charging was performed with a charging current of 1 C, a charging end voltage of 4.25 V, and a total charging time of 3 hours, and then a rest period of 10 minutes was provided. Then, constant current discharging was performed with a discharging current of 1 C and a discharging end voltage of 2.75 V, and then a rest period of 10 minutes was provided. The initial charging and discharging were performed by the above operations. As a result, the non-aqueous electrolyte storage element of Example 1 was obtained.

[0101] Furthermore, constant current discharge was performed at a discharge current of 0.2 C and a discharge end voltage of 2.75 V, and the negative electrode potential was measured after keeping the circuit open for 10 minutes or more. The negative electrode potential at 100% DOD after the initial charge and discharge was 0.48 V vs. Li / Li + It was.

[0102] [Example 2, Comparative Examples 1 and 2] Each of the nonaqueous electrolyte storage elements of Example 2 and Comparative Examples 1 and 2 was obtained in the same manner as in Example 1, except that the content of silicon oxide relative to the total amount of silicon oxide and graphite, which are the negative electrode active materials, and the coating mass of the negative electrode mixture were as shown in Table 1. 2 Table 1 shows the initial charge capacity (P, N) and initial irreversible capacity (Q'c, Q'a) per unit time, the initial irreversible capacity ratio (Q'c / Q'a), the initial charge capacity ratio (N / P), and the negative electrode potential at 100% DOD after the initial charge / discharge.

[0103] [Evaluation] (Capacity retention rate during charge / discharge cycles) The nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Examples 1 and 2 were subjected to a charge-discharge cycle test in the following manner. In a thermostatic chamber at 45°C, constant current and constant voltage charging was performed with a charge current of 1.0C, a charge cut-off voltage of 4.25V, and a total charge time of 3 hours, followed by a rest period of 10 minutes. Thereafter, constant current discharging was performed with a discharge current of 1.0C and a discharge cut-off voltage of 2.75V, followed by a rest period of 10 minutes. This charge-discharge cycle was repeated 50 times. The ratio of the discharge capacity at the 50th cycle to the discharge capacity at the 1st cycle in this charge-discharge cycle test was determined as the capacity retention rate in the charge-discharge cycle. The capacity retention rates in the charge-discharge cycle of each of the nonaqueous electrolyte storage elements of Examples 1 and 2 and Comparative Examples 1 and 2 obtained are shown in Table 1 and FIG. 5.

[0104] [Table 1]

[0105] As shown in Figure 5, the critical point is between 1.13 and 1.15 for the initial irreversible capacity ratio (Q'c / Q'a), and it can be seen that when the initial irreversible capacity ratio (Q'c / Q'a) is 1.15 or higher, the capacity retention rate during charge-discharge cycles is significantly improved.

[0106] In addition, the above-mentioned Patent Document 1 describes a non-aqueous electrolyte secondary battery using silicon oxide as a negative electrode, which is characterized in that: (1) a positive electrode containing a Li-containing transition metal oxide of a predetermined composition and SiO x and a negative electrode containing graphite, (2) by adjusting the initial charge / discharge efficiency of the positive electrode and the negative electrode in this way, the potential of the negative electrode when discharged to 2.5 V is lowered to 1.0 V or less on a Li basis, and (3) by setting the potential of the negative electrode to 1.0 V or less on a Li basis in this way, good charge / discharge cycle characteristics can be ensured (Patent Document 1

[0014] ). However, the initial charge / discharge efficiency (initial discharge capacity / initial charge capacity) of the positive electrode in the above Comparative Examples 1 and 2 is about 0.87 (≒166.9 / 191.0), while the initial charge / discharge efficiency of the negative electrode is about 0.90 (≒401.7 / 448.0), so the initial charge / discharge efficiency of the positive electrode is lower. In addition, in both of the above Comparative Examples 1 and 2, the negative electrode potential in a state of 100% DOD is 1.0 V vs. Li / Li + That is, the capacity retention rate in the charge-discharge cycle is not sufficient in the above-mentioned Comparative Examples 1 and 2, although they are the invention of Patent Document 1. That is, it can be said that there is a limit to the improvement of the capacity retention rate in the charge-discharge cycle even if the focus is only on the magnitude relationship of the initial charge-discharge efficiency of the positive electrode and the negative electrode, as in the invention of Patent Document 1. In contrast, it can be seen that the capacity retention rate in the charge-discharge cycle can be significantly improved by focusing on the ratio of the absolute amount of the irreversible capacity of the positive electrode and the negative electrode and setting the ratio to a predetermined value (1.15) or more.

[0107] [Example 3] (Measurement of irreversible capacity per unit mass of positive electrode active material) The positive electrode active material is LiNi, a lithium transition metal composite oxide with an α-NaFeO2 type crystal structure.0.8 Mn 0.1 Co 0.1 O2 was prepared. This positive electrode active material has an upper limit charge potential of 4.33 V vs. Li / Li + The discharge end potential is 2.85 V vs. Li / Li + In this case, the initial charge capacity is 230.7mAh / g, the initial discharge capacity is 199.2mAh / g, and the initial irreversible capacity is 31.5mAh / g.

[0108] (Measurement of irreversible capacity per unit mass of negative electrode active material) A mixture of silicon oxide (SiO) and graphite (Gr) was prepared as the negative electrode active material. The mass ratio of silicon oxide to graphite was 10:90. This negative electrode active material had a minimum charge potential of 0.02 V vs. Li / Li. + The discharge end potential is 2.0 V vs. Li / Li + In this case, the initial charge capacity is 476.7mAh / g, the initial discharge capacity is 435.9mAh / g, and the initial irreversible capacity is 40.8mAh / g.

[0109] (Preparation of positive and negative electrodes) A positive electrode mixture paste was prepared containing the positive electrode active material, acetylene black (AB), and polyvinylidene fluoride (PVDF) in a ratio of 93:3.5:3.5 (solid weight equivalent) and N-methylpyrrolidone (NMP) as a dispersion medium. This positive electrode mixture paste was applied to a strip of aluminum foil as a positive electrode substrate and dried to remove the NMP. 2 The amount of positive electrode mixture paste applied per electrode is 1.655 mg / cm2 in terms of solid content. 2 This was pressed with a roller press to form a positive electrode active material layer, which was then dried under reduced pressure to obtain a positive electrode. 2 The initial charge capacity (P) per 2 , 1cm 2 The initial irreversible capacity (Q'c) per 2 It became.

[0110] A negative electrode mixture paste was prepared containing the negative electrode active material (SiO+Gr):styrene butadiene rubber (SBR):carboxymethyl cellulose (CMC) in a mass ratio of 97:2:1 (solid content equivalent) and using water as a dispersion medium. This negative electrode mixture paste was applied to both sides of a strip-shaped copper foil current collector as a negative electrode substrate, and then dried to remove the water. 2 The amount of negative electrode mixture paste applied per unit area is 0.90 mg / cm2 in terms of solid content. 2 This was pressed with a roller press to form a negative electrode active material layer, which was then dried under reduced pressure to obtain a negative electrode. 2 The initial charge capacity per unit (N) is 416.4 μAh / cm 2 , 1cm 2 The initial irreversible capacity (Q'a) per 2 It became.

[0111] The ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode thus obtained (Q'c / Q'a) was 1.36. 2 First charge capacity (P) per cm of negative electrode 2 The ratio (N / P) of the initial charge capacity (N) per cell was 1.17.

[0112] A nonaqueous electrolyte was prepared in the same manner as in Example 1, and the fabrication and initial charge / discharge were carried out in the same manner as in Example 1, except that the above positive electrode and negative electrode were used, to obtain a nonaqueous electrolyte storage element of Example 3.

[0113] Furthermore, a constant current discharge was performed at a discharge current of 0.2 C and a discharge end voltage of 2.75 V, and the negative electrode potential was measured after keeping the circuit open for 10 minutes or more. The negative electrode potential at 100% DOD after the initial charge and discharge was 0.524 V vs. Li / Li + It was.

[0114] [Examples 4 to 6] Each of the nonaqueous electrolyte storage elements of Examples 4 to 6 was obtained in the same manner as in Example 3, except that the coating mass of the positive electrode mixture and the coating mass of the negative electrode mixture were as shown in Table 2.2 Table 2 shows the initial charge capacity (P, N) and initial irreversible capacity (Q'c, Q'a) per unit time, the initial irreversible capacity ratio (Q'c / Q'a), the initial charge capacity ratio (N / P), and the negative electrode potential at 100% DOD after the initial charge / discharge.

[0115] [Evaluation] (Discharge voltage retention rate and energy retention rate in the range of silicon oxide usage during charge / discharge cycle) A charge-discharge cycle test was carried out for each of the obtained nonaqueous electrolyte storage elements of Examples 3 to 6 in the following manner. In a thermostatic chamber at 25°C, constant current and constant voltage charging was carried out at a charge current of 1.0C, a charge cut-off voltage of 4.25V, and a total charge time of 3 hours, followed by a rest period of 10 minutes. Thereafter, constant current discharging was carried out at a discharge current of 1.0C and a discharge cut-off voltage of 2.75V, followed by a rest period of 10 minutes. This charge-discharge cycle was carried out 50 times. In the negative electrode of each of the nonaqueous electrolyte storage elements of Examples 3 to 6, the range of DOD 50% to 100% was set as the region in which silicon oxide was mainly used. The ratio of the average discharge voltage in the above range in the 50th cycle to the average discharge voltage in the range of DOD 50% to 100% in the first cycle in the above charge-discharge cycle test was obtained as the average discharge voltage retention rate. In addition, the ratio of the energy discharged in the above range in the 50th cycle to the energy discharged in the range of DOD 50% to 100% in the first cycle in the above charge-discharge cycle test was obtained as the energy retention rate. The obtained average discharge voltage retention rate and energy retention rate in the charge-discharge cycle of each of the nonaqueous electrolyte storage elements of Examples 3 to 6 are shown in Table 2 and Figures 6 and 7.

[0116] [Table 2]

[0117] As shown in Table 2 and Figures 6 and 7, when the initial irreversible capacity ratio (Q'c / Q'a) is 1.55 or less, the discharge voltage retention rate and energy retention rate are significantly improved in the utilization range of silicon oxide in the charge-discharge cycle (the range of DOD 50% to 100% in each of the nonaqueous electrolyte storage elements of Examples 3 to 6).

[0118] 8 shows an example of a discharge curve of a negative electrode in which the accumulation of the highly crystalline phase occurs, and a discharge curve of a negative electrode in which the accumulation of the highly crystalline phase is suppressed, in a nonaqueous electrolyte storage element including a negative electrode containing silicon oxide. When the accumulation of the highly crystalline phase occurs, the discharge potential of the negative electrode increases in the range of DOD 60% to 100%, and therefore the average discharge voltage of the nonaqueous electrolyte storage element including the negative electrode decreases. [Industrial Applicability]

[0119] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0120] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 4' Positive lead 5 Negative terminal 5' Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A battery comprising a positive electrode and a negative electrode having a negative electrode active material containing silicon oxide, the positive electrode contains a lithium transition metal composite oxide having an α-NaFeO 2 type crystal structure or a spinel type crystal structure; The content of the silicon oxide in the negative electrode active material is 4 mass% or more, The nonaqueous electrolyte electricity storage element has a ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode of 1.15 or more and 1.55 or less.

2. The open circuit potential of the negative electrode at a discharge depth of 100% is 0.485 V vs. Li / Li + The nonaqueous electrolyte storage element according to claim 1 .

3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the negative electrode further comprises graphite.

4. Producing a positive electrode comprising a lithium transition metal composite oxide having an α-NaFeO 2 type crystal structure or a spinel type crystal structure; Producing a negative electrode having a negative electrode active material with a silicon oxide content of 4% by mass or more; and Initial charging and discharging Equipped with A method for producing a nonaqueous electrolyte electricity storage element, wherein a ratio of the initial irreversible capacity of the positive electrode to the initial irreversible capacity of the negative electrode is 1.15 or more and 1.55 or less.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2006294469A

  • Nonaqueous secondary battery

    JP2011113863A

  • Manufacturing method of electrode for lithium ion secondary battery

    JP2013089452A

  • Lithium ion secondary battery

    JP2013242997A

  • Negative electrode active material layer for lithium ion secondary battery, lithium ion secondary battery, negative electrode mixture for lithium ion secondary battery, and method for producing negative electrode active material layer for lithium ion secondary battery

    JP2014120459A